Guerrilla Girls: the art of behaving badly - Guerrilla Girls (Group of artists) (Chronicle Books, 2020)
Guerrilla Girls: The Art of Behaving Badly is the first book to catalog the entire career of the Guerrilla Girls from 1985 to present. The Guerrilla girls are a collective of political feminist artists who expose discrimination and corruption in art, film, politics, and pop culture all around the world. This book explores all their provocative street campaigns, unforgettable media appearances, and large-scale exhibitions. Captions by the Guerrilla Girls themselves contextualize the visuals. Explores their well-researched, intersectional takedown of the patriarchy In 1985, a group of masked feminist avengers'known as the Guerrilla Girls'papered downtown Manhattan with posters calling out the Museum of Modern Art for its lack of representation of female artists. They quickly became a global phenomenon, and the fearless activists have produced hundreds of posters, stickers, and billboards ever since. More than a monograph, this book is a call to arms. This career-spanning volume is published to coincide with their 35th anniversary. Perfect for artists, art lovers, feminists, fans of the Guerrilla Girls, students, and activists You'll love this book if you love books like Wall and Piece by Banksy, Why We March: Signs of Protest and Hope by Artisan, and Graffiti Women: Street Art from Five Continents by Nicholas Ganz.
Keywords: 1900-1999; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; amériques; approches et analyses; artivisme; arts; arts visuels et médiatiques; com5170; corps; cours; discipline; histoire de l'art; justice sociale; militance; patriarcat; premier cycle; périodes historiques; rapports sociaux de sexe; représentation des femme*; régions géographiques; sexisme; sofia; systèmes d'oppressions; thématiques; travail; états-unis

Desire change: contemporary feminist art in Canada - Davis, Heather M. (Heather Margaret); Mentoring Artists for Women's Art (McGill-Queen's University Press ;, 2017)
"In the resistance to the violence of gender-based oppression, vibrant - but often ignored - worlds have emerged, full of nuance, humour, and beauty. Correcting a glaring omission of writing about contemporary feminist work by Canadian artists, Desire Change considers the resurgence of feminist art, thought, and practice in the past decade by examining artworks that respond to themes of diversity and desire. Essays by historians, artists, and curators present an overview of a range of artistic practices including performance, installation, video, textiles, and photography. Contributors address the desire for change through three central frames: how feminist art has significantly contributed to the complex understanding of gender as it intersects with sexuality and race; the necessary critique of patriarchy and institutions as they relate to colonization within the Canadian national-state; and the ways in which contemporary critiques are formed and expressed. The resulting collection addresses art through an activist lens to examine intersectional feminism, decolonization, and feminist institution building in a Canadian context. Heavily illustrated with representative works, Desire Change raises both the stakes and the concerns of contemporary feminist art, with an understanding that feminism is always and necessarily plural."– Provided by publisher.
Keywords: 2000 à aujourd'hui; 2010-2019; amériques; approches et analyses; arts; canada; cours; discipline; femmes* artistes; féminisme décolonial; har4600; histoire de l'art; histoire et politique; intersectionnalité; patriarcat; premier cycle; périodes historiques; régions géographiques; sexisme; systèmes d'oppressions; thématiques

Au-delà du plaisir visuel: féminisme, énigmes, cinéphilie - Mulvey, Laura (Éditions Mimésis, 2017)
En 1975, Laura Mulvey publie Plaisir visuel et cinéma narratif, texte polémique qui met en lumière la manière dont la forme filmique serait structurée par l’inconscient de la société patriarcale. C’est l’essai fondateur des études féministes sur le cinéma. Rédigés entre 1975 et 2011, les textes choisis dans ce volume sont marqués par la redécouverte féministe de la psychanalyse et les transformations induites par le développement des technologies numériques. Qu’elle s’attache à des genres ou à des auteurs incontournables (le western, le mélodrame, Ophüls, Hitchcock, Godard), qu’elle incarne l’avènement d’un « spectateur pensif », qu’elle analyse les paradoxes de l’esthétique hollywoodienne ou la compilation de films de propagande coloniale, Laura Mulvey fait preuve d’une cinéphilie active et engagée.
Keywords: 1900-1999; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2010-2019; amériques; approches et analyses; arts; cinema hollywoodien; cinéma; com5170; communication; corps; cours; discipline; discours dominant; europe; har4600; histoire de l'art; histoire et politique; male gaze; patriarcat; premier cycle; périodes historiques; rapports sociaux de sexe; regard masculin; royaume-uni; régions géographiques; sofia; systèmes d'oppressions; thématiques; théorie du cinéma; états-unis

Feminist avant-garde: art of the 1970s : the Sammlung Verbund Collection, Vienna - Schor, Gabriele; Galleria nazionale d'arte moderna (Italie); Círculo de Bellas Artes (Madrid, Espagne); Palais des beaux-arts (Bruxelles, Belgique); Mjellby konstmuseum; Hamburger Kunsthalle; Photographers' Gallery; Museum Moderner Kunst (Autriche); Sammlung Verbund.; Schor, Gabriele; Galleria nazionale d'arte moderna (Italie); Círculo de Bellas Artes (Madrid, Espagne); et al. (Prestel, 2016)
Featuring a wide variety of work from artists both well-known and under the radar, this dynamic book reveals how women artists reclaimed control of the feminine image in photography, video, and performance art. This book documents a tectonic change in the way women portray themselves in art. Historically, women were depicted as a projection of male fantasies, prejudices, and relationships. However in the 1970s, for the first time, female artists began collectively to investigate visual representations of their own selves. They studied their own bodies and created the prospect of determined feminine identities. Editor Gabriele Schor explores the Feminist Avant-Garde to emphasize the role that these artists played for the last four decades. The works are provocative, radical, poetic, ironic, angry, cynical and heartfelt. The artists shared a collective consciousness that reassessed, and even rejected, what came before, turning to new ways of expression in the fields of photography, performance, film, and video. The collection SAMMLUNG VERBUND founded in 2004 in Vienna focuses on the feminist art movement of the 1970s as one of the main areas and is with 500 works the largest collection with this emphasis. Included are works by Eleanor Antin, Cindy Sherman, Ana Mendieta, Nil Yalter, Ketty La Rocca, Birgit Jürgenssen, Renate Bertlmann, Francesca Woodman and others. This important book emphasizes the accomplishments of women artists who have made a name for themselves while encouraging the young generation.
Keywords: 1900-1999; 1970-1979; approches et analyses; arts; biographie; corps; cours; discipline; femmes* artistes; har4600; histoire de l'art; patriarcat; premier cycle; périodes historiques; sexisme; systèmes d'oppressions; thématiques

« Your Body is a Battleground » De quelques objets de l'histoire de l'art - Mader, Rachel; Schweizer, Nicole (Nouvelles Questions Féministes, 2005)
Notre article s'articule autour des points suivants: comment la critique féministe de histoire de l'art a-t-elle déplacé le ou les «objets» autour desquels s'articulait traditionnellement la discipline? Quels nouveaux «objets» ont dès lors été constitués? Et comment, à l'épreuve de ceux-ci, les histoires de l'art féministes doivent-elles, elles aussi, constamment se repositionner? L'exemple paradigmatique du corps dans la performance des années 70 nous permet d'interroger dans un deuxième temps la façon dont les artistes elles-mêmes ont déplacé la définition de l'objet, et par conséquent aussi celle du sujet - de l'œuvre comme de la perception.
Number: 1
Keywords: 1900-1999; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; approches et analyses; artistes féministes; arts; corps; cours; discipline; femmes* artistes; har4600; histoire de l'art; histoire et politique; patriarcat; performance; premier cycle; périodes historiques; représentation des femme*; ressource en ligne; sex2283; sexisme; systèmes d'oppressions; thématiques

Differencing the canon: feminist desire and the writing of art's histories - Pollock, Griselda (Routledge, 1999)
In this major book, Griselda Pollock engages boldly in the culture wars over `what is the canon?` and `what difference can feminism make?` Do we simply reject the all-male line-up and satisfy our need for ideal egos with an all women litany of artistic heroines? Or is the question a chance to resist the phallocentric binary and allow the ambiguities and complexities of desire - subjectivity and sexuality - to shape the readings of art that constantly displace the present gender demarcations?
Keywords: approches et analyses; artistes féministes; arts; canon; cours; discipline; discours dominant; femmes* artistes; har4600; histoire de l'art; histoire et politique; patriarcat; premier cycle; ressource en ligne; sexisme; systèmes d'oppressions; thématiques

Pourquoi n'y-a-t-il pas eu de grands artistes femmes? - Nochlin, Linda (Femmes, art et pouvoir., 1993)
Première publication : 1991
Keywords: approches et analyses; arts; cours; discipline; domination masculine; fem1000; histoire de l'art; histoire et politique; inégalités; patriarcat; premier cycle; systèmes d'oppressions; thématiques; théories féministes

Surrealism and women - Caws, Mary Ann; Kuenzli, Rudolf E.; Raaberg, Gloria Gwen (MIT Press, 1991)
These sixteen illustrated essays present an important revision of surrealism by focusing on the works of women surrealists and their strategies to assert positions as creative subjects within a movement that regarded woman primarily as an object of masculine desire or fear.While the male surrealists attacked aspects of the bourgeois order, they reinforced the traditional patriarchal image of woman. Their emphasis on dreams, automatic writing, and the unconscious reveal some of the least inhibited masculine fantasies. The first resistance to the male surrealists' projection of the female figure arose in the writings and paintings of marginalized woman artists and writers associated with Surrealism. The essays in this collection explore the complexity of these women's works, which simultaneously employ and subvert the dominant discourse of male surrealists.
Keywords: 1900-1999; approches et analyses; arts; cours; discipline; discours dominant; femmes* artistes; har4600; histoire de l'art; histoire et politique; patriarcat; premier cycle; périodes historiques; sexisme; systèmes d'oppressions; thématiques

The Feminist Critique of Art History - Gouma-Peterson, Thalia; Mathews, Patricia (The Art Bulletin, 1987)
Art criticism and art history from a feminist perspective are recent phenomena, emerging only during the last fifteen years. They have, in their short history, moved from a first generation in which "the condition and experience of being female" was emphasized, to a second generation, beginning in the late 1970s, influenced by feminist criticism in other disciplines and offering a more complex critique of both art and culture through an investigation of the production and evaluation of art and the role of the artist. In this survey, we propose, first, to outline the history of feminist art and art history, then to discuss the interrelated themes in each, and, finally, in the concluding and pivotal sections (IV and V), to discuss various feminist art-critical and art-historical methodologies.
Number: 3
Keywords: 1900-1999; approches et analyses; art moderne; artistes féministes; arts; corps; cours; critique d'art; discipline; discours dominant; femmes* artistes; har4600; histoire de l'art; histoire et politique; maternité; patriarcat; premier cycle; périodes historiques; représentation; sexisme; sexualité; systèmes d'oppressions; thématiques

The obstacle race: the fortunes of women painters and their work - Greer, Germaine (Farrar, Straus, Giroux, 1979)
If men and women are equally capable of genius, why have there been no female artists of the stature of Leonardo, Titian or Poussin? In seeking to answer this question, Germaine Greer introduces us to major but underestimated figures in the history of Western painting–Angelica Kauffmann, Natalia Goncharova, Suzanne Valadon, Berthe Morisot, Kathe Köllwitz–and produces a brilliantly incisive and richly illustrated study. She explains the obstacles as both external and surmountable and internal and insurmountable in the race for achievement.
Section: 373 pages
Keywords: 1900-1999; amérique du nord; amériques; approches et analyses; arts; cours; discipline; discours dominant; europe; femmes* artistes; har4600; histoire de l'art; histoire et politique; patriarcat; périodes historiques; régions; régions géographiques; sexisme; systèmes d'oppressions; thématiques; théorie de l'art

Être féministe et objectifier son propre corps : les autoportraits d'Hannah Wilke - Institut de recherches et d'études féministes
Est-ce que c'est féministe de se mettre nue devant une caméra ? Comment peut-on jouer avec la caméra jusqu'à reprendre pouvoir sur notre image ? Amélie Fontaine-Dupont nous partage ses résultats de recherche sur l'artiste Hannah Wilke et montre comment l'auto-objectification sexuelle peut être une posture féministe et permettre d’approfondir la réflexion sur la culpabilisation et la répréhension des femmes qui font usage de leur corps et de leur sexualité à des fins d’émancipation. Biographie: Amélie Fontaine-Dupont est étudiante à la maîtrise en histoire de l'art à l'UQAM et détient un baccalauréat en histoire de l'art de l'Université Laval. S’intéressant autant aux études féministes qu’à l’art contemporain, ses recherches actuelles portent sur l'auto-objectification sexuelle comme forme d’agentivité et d’activisme féministe dans les œuvres performatives de l'artiste états-unienne Hannah Wilke. Amélie est membre étudiante de l'Institut de recherches et d'études féministes de l’UQAM et du Réseau québécois en études féministes. Elle occupe également le poste de responsable des communications de l'Association des cycles supérieurs en histoire de l'art de l'UQAM. En parallèle à ses études, elle travaille à la Galerie de l'UQAM et intervient ponctuellement en tant que médiatrice culturelle à l'occasion d'évènements artistiques et d’expositions. Enregistré durant la Tournée des cégeps à l’automne 2024 (https://iref.uqam.ca/babillard/tournee-des-cegeps-foire-feministe-feministes-dans-la-cite/)par Rajae Anys et Juliette Chevet. Ecrit et monté par Juliette Chevet. Avec le soutien financier du CRSH
Keywords: 1900-1999; 1970-1979; 1980-1989; amérique; approches et analyses; arts; corps; discipline; foire féministe; histoire de l'art; militance; patriarcat; régions géographiques; sexisme; systèmes d'oppressions; thématiques; états-unis